Acute effects of insulin on circulating natriuretic peptide levels in humans. - Katherine N Bachmann; Serpil Muge Deger; Aseel Alsouqi; Shi Huang; Meng Xu; Jane F Ferguson; Yan Ru Su; Kevin D Niswender; T Alp Ikizler; Thomas J Wang (PLoS ONE, 2018)
The natriuretic peptide hormones play an important role in salt and blood pressure regulation. In observational studies, obesity and insulin resistance have been consistently associated with lower concentrations of natriuretic peptides. It has been proposed that insulin influences natriuretic peptide production.We sought to determine the acute effects of insulin administration on natriuretic peptide concentrations.31 men and women (11 lean, 10 overweight, and 10 obese), ages 30-70 years, without cardiovascular disease or overt diabetes underwent a hyperinsulinemic-euglycemic insulin clamp. Plasma concentrations of N-terminal pro atrial natriuretic peptide (NT-proANP) and N-terminal pro B-type natriuretic peptide (NT-proBNP) were measured at baseline and steady-state (the final 30 minutes of the clamp protocol).From baseline to steady-state, insulin levels increased from a mean level of 9.5 to 176.7 μU/ml (p<0.001). Over this period, circulating NT-proANP concentrations decreased by 9% (-1933 ng/L, p = 0.01). The changes in NT-proANP did not differ between lean, overweight, and obese individuals. Steady-state NT-proANP levels, adjusted for baseline, were lower in individuals with greater insulin resistance, independent of BMI. In contrast to NT-proANP, NT-proBNP levels did not change significantly during the clamp (p = 0.41).Insulin administration was associated with a moderate decrease in circulating NT-proANP, but not NT-proBNP. The lowest NT-proANP concentrations were found in insulin-resistant individuals. Further investigations are warranted to elucidate potential mechanisms underlying the effects of insulin on the cardiac hormonal axis.